Produção de crisântemo cultivado em diferentes substratos fertirrigados com fósforo, potássio e silício - Rodrigues, Tatiana Michlovská (2006)
The effect of different substrates and concentrations of phosphorous, potassium and silicon in solutions of fertirrigation (SF) were evaluated during the development of chrysanthemums (Dendranthema grandiflorum) cv. "Puritan". After 90 days of rooting, the number of inflorescences, leaves, stems per plant and vase, inflorescences diameter and plant height (cm) and dry matter of inflorescences, leaves, stems and the ratios leaf/stem and leaf/inflorescence were determined. Leaf critical levels and nutrient accumulation on shoots were estimated through chemical analyses of leaves, inflorescences and stems for the phosphorous experiment. A randomized completely experimental design in 2x5 factorial scheme with four replications was used with two substrates (Vida Verde® - commercial substrate for chrysanthemum growth) (SC) and coconut fiber [Golden Mix Mixto (T-40) - Amafibra®] (FC) and five concentrations of P, K and Si. In the first experiment, the P concentrations tested were 25, 50, 100, 200 and 400 mg L-1. In the second experiment with potassium and the third with silicon, the following concentrations were tested 25; 50; 100; 200 and 400 mg L-1 and 0; 12.5; 25; 37.5; and 50 mg L-1, respectively. The use of 43 and 80 mg L-1 P in the SF provided the maximum economic production (MPE) in the substrates FC and SC, respectively. Leaf nutrient levels associated to MPE in the substrates were (g kg-1): N=56.8; P=2.2; K=21.6; Ca=22.1; Mg=4.9; S=4.2; (mg kg-1): B=51.7; Cu=8.8; Fe=372.2; Mn=600.0 and Zn=93.8 for plants grown in FC and (g kg-1): N=52.3; P=1.4; K=17.1; Ca=23.5; Mg=5.9; S=3.6; (mg kg-1): B=36.2; Cu=4.5; Fe=377.4; Mn=517.8 and Zn=45.2 for plants grown in SC. The nutritional demand related to MPE in both substrates followed the sequence: N>K>Ca>P>Mg>S>Mn>Fe>Zn>B>Cu. Plants of chrysanthemum grown in FC can reduce in up to 46.25% the P concentration in the SF in order to obtain plants with good quality. The use of 400 mg L-1 of potassium in the fertirrigated solution provided the higher production in both substrates however, the substrate FC formed plants with better quality compared with the commercial substrate. The use 37.5 mg L-1 of silicon in the fertirrigated solution provided plants with better quality in both substrates however, the substrate SC formed plants with better quality compared with the FC substrate.